2017
DOI: 10.1021/acsami.6b13397
|View full text |Cite
|
Sign up to set email alerts
|

Design of Electrically Conductive Structural Composites by Modulating Aligned CVD-Grown Carbon Nanotube Length on Glass Fibers

Abstract: Function-integration in glass fiber (GF) reinforced polymer composites is highly desired for developing lightweight structures and devices with improved performance and structural health monitoring. In this study, homogeneously aligned carbon nanotube (CNT) shell was in situ grafted on GF by chemical vapor deposition (CVD). It was demonstrated that the CNT shell thickness and weight fraction can be modulated by controlling the CVD conditions. The obtained hierarchical CNTs-GF/epoxy composites show highly impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 44 publications
4
44
0
Order By: Relevance
“…The D peak was detected at 1344 cm -1 , results from the out-of-plane vibrations of sp 3 atoms, which is an indication of the structural defects of carbon atoms while the G peak was located at 1593 cm -1 , attributed to the in-plane vibrations of sp 2 bonded atoms. The I g /I d ratio was calculated as 1.08±0.04, a similar result obtained by He et al [24] with CVD-grown CNTs on micron-sized glass fibers, indicating defective CNTs resulted from low synthesis temperatures.…”
Section: Fig 5 (A) Sem Image Of the Cnts-pbi Nanofibrous Substratessupporting
confidence: 87%
“…The D peak was detected at 1344 cm -1 , results from the out-of-plane vibrations of sp 3 atoms, which is an indication of the structural defects of carbon atoms while the G peak was located at 1593 cm -1 , attributed to the in-plane vibrations of sp 2 bonded atoms. The I g /I d ratio was calculated as 1.08±0.04, a similar result obtained by He et al [24] with CVD-grown CNTs on micron-sized glass fibers, indicating defective CNTs resulted from low synthesis temperatures.…”
Section: Fig 5 (A) Sem Image Of the Cnts-pbi Nanofibrous Substratessupporting
confidence: 87%
“…This ratio indicates that the amount of defective carbons are more than graphitic carbons. The IG/ID around 1 is a typical value for CNTs that were grown onto fibers at around 600 °C growth temperature [28].…”
Section: Resultsmentioning
confidence: 99%
“…CNTs excluding other compounds that were found in TGA of Neat/GF and Fe +3 /GF. He et al [28] studied CNT loadings varying between 0.2 and 7 wt%, and found that enhancements in both mechanical and electrical properties remained similar for CNT loadings greater than 3 wt%. Therefore, 5 wt% CNT loading obtained in this work can be interpreted as appropriate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations